The responsibility of state officials for violating the law on public service - Bereza, Nadiia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to coverage and analysis of civil servants for violating the law on public service. According to the Law of Ukraine «On State Service», a civil servant (in Ukraine) - a citizen of Ukraine who has held the position of public service in government, another public body, its staff (Secretariat) receives a salary from the state budget and has set credentials for the job are directly related to the performance of tasks and functions of the public body, and adheres to the principles of public service.That is, civil servants are individuals, which lies directly perform public functions in the territory, in particular public administration. Hence, the responsibility for violation of legislation on civil service is particularly interesting topic for research